2006
DOI: 10.1038/ni1380
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer T cells recognize diacylglycerol antigens from pathogenic bacteria

Abstract: Natural killer T (NKT) cells recognize glycosphingolipids presented by CD1d molecules and have been linked to defense against microbial infections. Previously defined foreign glycosphingolipids recognized by NKT cells are uniquely found in nonpathogenic sphingomonas bacteria. Here we show that mouse and human NKT cells also recognized glycolipids, specifically a diacylglycerol, from Borrelia burgdorferi, which causes Lyme disease. The B. burgdorferi-derived, glycolipid-induced NKT cell proliferation and cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
549
0
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 580 publications
(569 citation statements)
references
References 48 publications
11
549
0
9
Order By: Relevance
“…Whereas the ability of some previously described ligands of microbial origin -Plasmodium (and Trypanosoma) glycosylphosphatidylinositol (GPI) and Mycobacterium phosphatidylinositol mannoside (PIM) -to activate iNKT cells has been questioned, recent work has rigorously demonstrated that GSL-1 from Sphingomonas and BbGL-II from Borrelia undoubtedly stimulate NKT cells in a CD1d-dependent manner [49,[63][64][65]. It remains to be determined whether direct recognition of these glycolipids by iNKT cells is responsible for the iNKT cell-dependent anti-bacterial activity noted during infection with these bacteria [49,63].…”
Section: Exogenous Inkt Cell Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the ability of some previously described ligands of microbial origin -Plasmodium (and Trypanosoma) glycosylphosphatidylinositol (GPI) and Mycobacterium phosphatidylinositol mannoside (PIM) -to activate iNKT cells has been questioned, recent work has rigorously demonstrated that GSL-1 from Sphingomonas and BbGL-II from Borrelia undoubtedly stimulate NKT cells in a CD1d-dependent manner [49,[63][64][65]. It remains to be determined whether direct recognition of these glycolipids by iNKT cells is responsible for the iNKT cell-dependent anti-bacterial activity noted during infection with these bacteria [49,63].…”
Section: Exogenous Inkt Cell Antigensmentioning
confidence: 99%
“…iNKT cells have been shown to directly recognize α-linked glycosphingolipids and diacylglycerol antigens that are expressed by bacteria such as Sphingomonas, Ehrlichia and Borrelia burgdorferi in a CD1d-dependent manner [49,[63][64][65] (Figure 1C). The biological response to these glycolipid antigens includes the production of IFNγ and IL-4 by iNKT cells.…”
Section: How Do Inkt Cells Get Activated? Cognate Recognition and Actmentioning
confidence: 99%
“…Type 1 and type 2 NKT cells also express a number of NK cell stimulatory receptors, such as NK1.1 in mice and NKG2C and NKG2D in humans. While iNKT cells recognize a number of self [147,148] and microbial [149][150][151] glycosphingolipids, most of our understanding of NKT cells comes from studies of murine and human iNKT cells stimulated with the xenogeneic glycolipid, agalactosylceramide (a-GC). Upon activation with a-GC in vitro, iNKT cells can kill target cells and secrete a diverse range of growth factors and cytokines [144][145][146].…”
mentioning
confidence: 99%
“…Bacteria such as Sphingomonas, Ehrlichia and Borrelia synthesize lipid antigens that form antigenic complexes with CD1d and stimulate iNKT cells [11,12,30]. These bacteria reach Ly, where they release the antigenic lipids.…”
Section: Lipid Traffic Within Cellsmentioning
confidence: 99%
“…Whether they are transported by cytoplasmic LTP remains to be investigated. These two glycolipid antigens can also be released by infected cells and become internalized by non-infected CD1-positive APC, thus allowing their cross-presentation [29].Bacteria such as Sphingomonas, Ehrlichia and Borrelia synthesize lipid antigens that form antigenic complexes with CD1d and stimulate iNKT cells [11,12,30]. These bacteria reach Ly, where they release the antigenic lipids.…”
mentioning
confidence: 99%